(untitled) (Bangladesh Journal of Medical Physics, 2013)
Osteoporosis or bone loss affects many people, particularly the aged women, and leads to disabling bone fractures. An early diagnosis could provide preventive management. However, available bone densitometry equipment are very expensive and not available widely in the Third World. The present work presents the design & development of an innovative low cost bone densitometer based on conventional X-ray equipment available widely. The main innovation is the incorporation of a stack of aluminium with varying thickness placed beside the limb of a patient while taking an X-ray image. Then the optical density of the bone area in the developed film is compared to that from the aluminium stack, which eliminates variations due to all other processing factors, and gives a measure of the bone density. A low cost device has been developed to measure the optical density of the X-ray film over a circular area of about 1cm to give an average reading, which is more appropriate than spot metering in this application. Preliminary measurements of a few human subjects using this equipment clearly indicate the differences obtained due to expected osteoporosis. Calibration with standard bone densitometry equipment could provide values in standard units. This low cost innovative method and equipment appears to provide a low cost alternative to the diagnosis of osteoporosis. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14693 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 95-100